Lateral response of offshore wind turbine monopile foundations in sloping ground under scour condition - Javad Saeidaskari; Raju Datla; Rita Sousa (Marine Georesources & Geotechnology, 2026)

Oscillating surge wave energy converter using a novel above-water power takeoff with belt-arc speed amplification - Jia Mi; Jianuo Huang; Xiaofan Li; Alaa Ahmed; Lisheng Yang; Uihoon Chung; Raju Datla; Muhammad Hajj; Lei Zuo (Ocean Engineering, 2024)

Resistance prediction and optimization of Tri-SWACH using hybrid surrogate model with particular consideration of outrigger layout - Guangshuo An; Gong Xiang; Xianbo Xiang; Raju Datla (Ocean Engineering, 2023)

Physical mapping of the wheat genes in low-recombination regions: radiation hybrid mapping of the C-locus - Anmol Kajla; Adam Schoen; Carl Paulson; Inderjit Singh Yadav; Kumari Neelam; Oscar Riera-Lizarazu; Jeff Leonard; Bikram S. Gill; Prakash Venglat; Raju Datla; Jesse Poland; Gary Coleman; et al. (Theoretical and Applied Genetics, 2023)

Comprehensive compositional assessment of bioactive compounds in diverse pea accessions - Xiumei Han; Leonid Akhov; Paula Ashe; Courteney Lewis; Leah Deibert; L. Irina Zaharia; Lily Forseille; Daoquan Xiang; Raju Datla; Matthew Nosworthy; Carol Henry; Jitao Zou; et al. (Food Research International, 2023)

Conserved, divergent and heterochronic gene expression during Brachypodium and Arabidopsis embryo development - Zhaodong Hao; Zhongjuan Zhang; Daoquan Xiang; Prakash Venglat; Jinhui Chen; Peng Gao; Raju Datla; Dolf Weijers (Plant Reproduction, 2021)
Key message Developmental and transcriptomic analysis of Brachypodium embryogenesis and comparison with Arabidopsis identifies conserved and divergent phases of embryogenesis and reveals widespread heterochrony of developmental gene expression. Abstract Embryogenesis, transforming the zygote into the mature embryo, represents a fundamental process for all flowering plants. Current knowledge of cell specification and differentiation during plant embryogenesis is largely based on studies of the dicot model plant Arabidopsis thaliana . However, the major crops are monocots and the transcriptional programs associated with the differentiation processes during embryogenesis in this clade were largely unknown. Here, we combined analysis of cell division patterns with development of a temporal transcriptomic resource during embryogenesis of the monocot model plant Brachypodium distachyon . We found that early divisions of the Brachypodium embryo were highly regular, while later stages were marked by less stereotypic patterns. Comparative transcriptomic analysis between Brachypodium and Arabidopsis revealed that early and late embryogenesis shared a common transcriptional program, whereas mid-embryogenesis was divergent between species. Analysis of orthology groups revealed widespread heterochronic expression of potential developmental regulators between the species. Interestingly, Brachypodium genes tend to be expressed at earlier stages than Arabidopsis counterparts, which suggests that embryo patterning may occur early during Brachypodium embryogenesis. Detailed investigation of auxin-related genes shows that the capacity to synthesize, transport and respond to auxin is established early in the embryo. However, while early PIN1 polarity could be confirmed, it is unclear if an active response is mounted. This study presents a resource for studying Brachypodium and grass embryogenesis and shows that divergent angiosperms share a conserved genetic program that is marked by heterochronic gene expression.

High-resolution mapping of the Mov-1 locus in wheat by combining radiation hybrid (RH) and recombination-based mapping approaches - Alexander Mahlandt; Nidhi Rawat; Jeff Leonard; Prakash Venglat; Raju Datla; Nathan Meier; Bikram S. Gill; Oscar Riera-Lizarazu; Gary Coleman; Angus S. Murphy; Vijay K. Tiwari (Theoretical and Applied Genetics, 2021)

Gene expression atlas of embryo development in Arabidopsis - Peng Gao; Daoquan Xiang; Teagen D. Quilichini; Prakash Venglat; Prashant K. Pandey; Edwin Wang; C. Stewart Gillmor; Raju Datla (Plant Reproduction, 2019)

Genome-wide identification and characterization of microRNA genes and their targets in flax (Linum usitatissimum) - Vitthal T. Barvkar; Varsha C. Pardeshi; Sandip M. Kale; Shuqing Qiu; Meaghen Rollins; Raju Datla; Vidya S. Gupta; Narendra Y. Kadoo (Planta, 2013)

Gene expression analysis in microdissected shoot meristems of Brassica napus microspore-derived embryos with altered SHOOTMERISTEMLESS levels - Mohamed Elhiti; Owen S. D. Wally; Mark F. Belmonte; Ainsley Chan; Yongguo Cao; Daoquan Xiang; Raju Datla; Claudio Stasolla (Planta, 2013)

Simple sequence repeat marker development from bacterial artificial chromosome end sequences and expressed sequence tags of flax (Linum usitatissimum L.) - Sylvie Cloutier; Evelyn Miranda; Kerry Ward; Natasa Radovanovic; Elsa Reimer; Andrzej Walichnowski; Raju Datla; Gordon Rowland; Scott Duguid; Raja Ragupathy (Theoretical and Applied Genetics, 2012)

Protein storage vacuoles of Brassica napus zygotic embryos accumulate a BURP domain protein and perturbation of its production distorts the PSV - Prapapan Teerawanichpan; Qun Xia; Sarah J. Caldwell; Raju Datla; Gopalan Selvaraj (Plant Molecular Biology, 2009)

Development and analysis of EST-SSRs for flax (Linum usitatissimum L.) - Sylvie Cloutier; Zhixia Niu; Raju Datla; Scott Duguid (Theoretical and Applied Genetics, 2009)

N-myristoyltransferase - Rajala V.S. Raju; Raju S.S. Datla; Terence N. Moyana; Rakesh Kakkar; Svein A. Carlsen; Rajendra K. Sharma (Molecular and Cellular Biochemistry, 2000)

Recombinant bovine spleen myristoyl CoA: Protein N-myristoyltransferase - Rajala V.S. Raju; Raju S.S. Datla; Rakesh Kakkar; Rajendra K. Sharma (Molecular and Cellular Biochemistry, 1998)

Promoter sequences from two different Brassica napus tapetal oleosin-like genes direct tapetal expression of β-glucuronidase in transgenic Brassica plants - Hai Ping Hong; Joanne H.E. Ross; Jean L. Gerster; Stamatis Rigas; Raju S.S. Datla; Polydefkis Hatzopoulos; Graham Scoles; Wilf Keller; Denis J. Murphy; Laurian S. Robert (Plant Molecular Biology, 1997)